2022
DOI: 10.33393/jcb.2022.2317
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs from urinary exosomes as alternative biomarkers in the differentiation of benign and malignant prostate diseases

Abstract: Introduction: Prostate cancer (PCa) is the second most frequently diagnosed cancer and the fifth most cancer-related cause of death worldwide. Various tools are used in the diagnosis of PCa, such as the Prostate-Specific Antigen (PSA) value or digital rectal examination. A final differentiation from benign prostate diseases such as benign prostatic hyperplasia (BPH) can often only be made by a transrectal prostate biopsy. This procedure carries post-procedural complications for the patients and may lead to hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Among others, these pathways contain several factors involved in the regulation of growth factors, cytokine-cytokine receptor interaction, apoptosis, cell cycle progression, cellular migration and invasion, and transcriptional regulation. MicroRNAs from urinary exosomes have already been suggested as alternative biomarkers in the differentiation of benign and malignant prostate diseases [51]. Our results suggest that microRNAs from PPM urine of CP/CPPS may be early prognostic biomarkers of malignant transformation of the prostate.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Among others, these pathways contain several factors involved in the regulation of growth factors, cytokine-cytokine receptor interaction, apoptosis, cell cycle progression, cellular migration and invasion, and transcriptional regulation. MicroRNAs from urinary exosomes have already been suggested as alternative biomarkers in the differentiation of benign and malignant prostate diseases [51]. Our results suggest that microRNAs from PPM urine of CP/CPPS may be early prognostic biomarkers of malignant transformation of the prostate.…”
Section: Discussionmentioning
confidence: 52%
“…Further, KEGG pathway analyses revealed that putative target genes of CP/CPPS‐specific upregulated microRNAs were significantly enriched for cancer‐associated pathways, such as “Prostate cancer,” “MAPK signaling pathway,” “FoxO signaling pathway,” and “Non‐small cell lung cancer.” Among others, these pathways contain several factors involved in the regulation of growth factors, cytokine–cytokine receptor interaction, apoptosis, cell cycle progression, cellular migration and invasion, and transcriptional regulation. MicroRNAs from urinary exosomes have already been suggested as alternative biomarkers in the differentiation of benign and malignant prostate diseases [ 51 ]. Our results suggest that microRNAs from PPM urine of CP/CPPS may be early prognostic biomarkers of malignant transformation of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited medical fields have investigated urinary microRNA profiles. Examples are metabolic diseases, chronic kidney disease, and cancers such as clear cell renal cell carcinoma, and prostate cancer [8,13–16]. The main innovation of this study was to explore urinary microRNAs as a novel resource to be potentially utilized for monitoring the pregnancy course.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited medical fields have investigated urinary microRNA profiles. Examples are metabolic diseases, chronic kidney disease, and cancers such as clear cell renal cell carcinoma, and prostate cancer [8,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…For urinary miRNAs, the majority of papers are related to cancer biomarker discovery (i.e., prostate cancers) and to the identification of small RNAs or miRNAs able to discriminate, for example, prostate cancers from benign prostate hyperplasia (BPH). In fact, Markert and collaborators used the random forest method to identify candidate small RNAs ( Markert et al, 2021 ), and in other studies the same group focused on miRNAs ( Holdmann et al, 2022 ).…”
Section: Artificial Intelligence and Systems Biology: From Diagnosis ...mentioning
confidence: 99%